Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. The degree of possession of mathematics teachers in the governorates of South Al-Batinah  and Al-Dakhiliyah in the Sultanate of Oman of the concepts of artificial intelligence, its applications and their attitudes towards itMs. Kothar Khalfan Abdullah Al-Jadeedi, Dr. Mohammad Nassir Saif Al-Riyami, Dr. Nassir Salim Nassir Al-Mazidi, Dr. Mahmood Nassir Al-Saqri2. The role of video games in the development of kindergarten children’s creative thinking skills  from the point of view of the instructorsMs. Ghadeer Hamad Alamar3. Digital Citizenship in Omani Schools: Exploring the Integration of Digital Citizenship Dimensions by Social Studies Teachers in the Educational Context of Basic Education SchoolsDr. Humaid Muslem Alsaidi., Mr. Fahad Abdullah Albalushi., Mr. Mohammed Said Alkaabi., Ms. Aysha Abdullah Albirikia4. Utilization of Automatic Speech Recognition Technology in English Language Teaching: A Systematic Review (2020-2023)Ms. Dina Mohammed Alazwari5. Role of the teacher in Activating, Through Classroom Environment and Utilization of media learning Resources, the Teaching of the Geography course to third Grade (Year) Female students  at the Girl School in the Holy City of MakkahMs. Aliaa Hameid Maghrapi, Dr. Fawzi Saleh Banjar6. The reality of using virtual classrooms in teaching English to the primary stage from the perspective of their teachers: A field studyMs. Shamma Suliman Aljurijeer7. How to development of conceptual understanding using virtual laboratories among second-year secondary school studentsDr. Abdulaziz Mohammed Hamdi8. The Effectiveness of an Innovative Mobile Application in Self-Regulation and Metacognitive Awareness Among Eighth Grade Students in the Sultanate of OmanDr. Huda Ali Said Al-Hosni, Prof. Sulaiman Mohammed Sulaiman Al-Balushi, Ms. Asmaa Hamed Gareeb Al-Salmi , Ms. Zahra Saif Mohammed Al-Shukaili
Keywords: Journal of Curriculum and Teaching Methodology